Cu-based ultralow-temperature catalyst for simultaneously reducing NOX and SO2, preparation method and application

By developing Cu-based ultra-low temperature catalysts and reducing NOX and SO2 using CO, the problem of lack of simultaneous reduction catalysts in the prior art is solved, efficient denitrification and desulfurization are achieved, pollution is avoided, and equipment investment is simplified.

CN119549161APending Publication Date: 2025-03-04XIAN RES INST OF CHINA COAL TECH & ENG GRP CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411349117.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

There is a lack of catalysts that can simultaneously reduce NOX and SO2 in the prior art, resulting in low denitrification and desulfurization efficiency and pollution problems such as NH3 escape.

Method used

A Cu-based ultra-low temperature catalyst was developed. By combining Al2O3, CeO2 and ZrO2 as support, it was combined with copper salt, cobalt salt, iron salt and palladium salt to form a CuO-CoO-Fe2O3-Pd/(Al2O3-CeO2-ZrO2) catalyst system, and using CO as a reducing agent to achieve the reduction of NOX and SO2.

Benefits of technology

The synchronous removal of NOX and SO2 has been achieved, which improves the denitrification and desulfurization efficiency, avoids NH3 escape, simplifies equipment investment, and is compatible with new and existing factory layouts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a Cu-based ultralow-temperature catalyst capable of simultaneously reducing NOX and SO2 as well as a preparation method and application of the Cu-based ultralow-temperature catalyst. The preparation method comprises the following steps: mixing Al2O3, CeO2 and ZrO2 in a mass ratio of 100: (4-6): (3-4) to obtain a carrier raw material; sequentially carrying out ball milling, drying and screening on the carrier raw material to obtain carrier powder; the preparation method comprises the following steps: dissolving a formula amount of active component in deionized water to obtain an active component solution, and compounding copper salt, cobalt salt, iron salt and palladium salt to obtain the active component solution; dipping the carrier powder into the active component solution, and sequentially carrying out standing, drying and roasting treatment to obtain precursor powder; mixing the precursor powder, an adhesive and deionized water, and stirring at a constant temperature to prepare active slurry; adding the pretreated matrix into the active slurry, and carrying out vacuum impregnation treatment to obtain an impregnated material, wherein the volume ratio of the matrix to the active slurry is 1: 3; and drying and calcining the obtained impregnated material to obtain the catalyst. In the precursor powder, the mass ratio of the carrier raw material to the active component is (77-87): (13-23).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of denitration, and in particular to a method for simultaneously reducing NO X Cu-based ultra-low temperature catalyst for catalytic oxidation and SO2, preparation method and application. Background Art

[0002] Sulfur dioxide (SO2) and nitrogen oxides (NO X ) account for more than 90% of the total emissions, SO2 and NO X It is an important atmospheric pollutant that can cause acid rain, photochemical smog, and damage the ozone layer, seriously endangering the environment and human health. X Removal technology, however, the current high-temperature V-series catalysts have great deficiencies during operation, so low-temperature SCR catalysts have become a research hotspot. At present, low-temperature catalysis usually adds NH3 as a reducing agent, which not only has low desulfurization and denitrification efficiency, but also inevitably causes NH3 to escape, resulting in secondary pollution problems, and the presence of amino products has certain hidden dangers to the safety of the site. Therefore, using CO as a reducing agent is more advantageous from the perspective of cost and environmental protection. And from a thermodynamic point of view, CO is a good reducing agent, and it is feasible to use it for the reduction of SO2. With the help of a catalyst, CO is used as a reducing agent to reduce SO2 to sulfur, so as to achieve the effect of purifying SO2 and recovering sulfur.

[0003] At present, the research on denitrification reaction is basically above 180℃, and there are few studies on the ultra-low temperature range below 180℃. There are even fewer studies on denitrification and desulfurization reactions using CO as a reducing agent.

[0004] Using CO in flue gas as a reducing agent to convert SO2 and NO X Reduction to elemental sulfur and N2 can produce SO2 and NO X However, this reaction can only be carried out in the presence of a catalyst, but the existing technology lacks the corresponding catalyst. Therefore, it is urgent to develop a catalyst that can simultaneously reduce NO X and SO2 catalyst. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a method for simultaneously reducing NO X Cu-based ultra-low temperature catalyst for reducing NO and SO2, preparation method and application thereof, to solve the problem that the prior art lacks the ability to simultaneously reduce NO X and technical issues of catalysts for SO2.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0007] A simultaneous reduction of NO X A method for preparing a Cu-based ultra-low temperature catalyst for catalyzing SO2 and SO2, characterized in that it comprises the following steps:

[0008] Step 1, mixing Al2O3, CeO2 and ZrO2 in a mass ratio of 100:(4-6):(3-4) to obtain a carrier raw material; ball milling, drying and sieving the carrier raw material in sequence to obtain a carrier powder;

[0009] Step 2, dissolving the active component in a formula amount in deionized water to obtain an active component solution, wherein the active component is compounded from copper salt, cobalt salt, iron salt and palladium salt;

[0010] Step 3, immersing the carrier powder obtained in step 1 in the active component solution obtained in step 2, and sequentially performing standing, drying and calcining treatments to obtain a precursor powder;

[0011] Step 4, mixing the precursor powder, the binder and deionized water, and stirring at a constant temperature to obtain an active slurry;

[0012] Step 5, adding the pretreated substrate to the active slurry for vacuum impregnation to obtain an impregnated product, wherein the volume ratio of the substrate to the active slurry is 1:3; drying and calcining the obtained impregnated product to obtain;

[0013] In the precursor powder, the mass ratio of the carrier powder to the active component is (77-87):

[0014] (13~23).

[0015] The present invention also has the following technical features:

[0016] Specifically, the carrier raw material is ball-milled, dried and sieved in sequence to obtain the carrier powder as described in step 1, comprising: a ball-milling speed of 300 to 600 r / min, a ball-milling time of 24 to 36 h, and during the ball-milling process, deionized water is added to the ball mill, and the solid-liquid ratio of the carrier raw material to the deionized water is 1.0:

[0017] (0.4~0.6), the mass ratio of grinding balls to carrier raw materials is (5.0~10.0):1.0; the drying temperature is 70~110℃, the drying time is 30min~60min; sieve through a 100 mesh sieve.

[0018] Furthermore, in the active components, the copper salt is calculated as CuO, the cobalt salt is calculated as CoO, the iron salt is calculated as Fe2O3, and the palladium salt is calculated as Pd, and the mass ratio is CuO:CoO:Fe2O3:Pd=(2~8):(5~7):(1~2):(0.5~0.6).

[0019] Furthermore, in step 3, the standing time is 20 to 30 hours; the drying temperature is 90 to 110° C., and the drying time is 12 to 18 hours; the roasting temperature is 700 to 750° C., and the roasting time is 4 to 6 hours.

[0020] Furthermore, the adhesive is selected from one or more of hydroxymethyl cellulose, polyvinyl alcohol and polyvinyl acetate.

[0021] Furthermore, in step 4, the mass ratio of the precursor powder to deionized water is 1:

[0022] (4.5~5.5), constant temperature stirring temperature is 50~100℃, constant temperature stirring time is 3~5h.

[0023] Furthermore, in step 5, the vacuum degree of the vacuum impregnation treatment is 10 -3 Pa~10 -5 Pa, the impregnation time is 2 to 5 hours; the drying temperature is 105 to 200°C, and the drying time is 10 to 15 hours; the calcination temperature is 480 to 530°C, and the calcination time is 5 to 8 hours.

[0024] Furthermore, the matrix is ​​selected from one or more of a cordierite matrix, a vermiculite matrix, a mullite matrix and a attapulgite matrix;

[0025] The pretreatment comprises: adding the matrix raw material into a dilute nitric acid solution with a mass fraction of 3-5% and soaking it for 0.5-1.0h to obtain a slurry; circulating deionized water to remove the residual acid in the slurry, and adjusting the pH of the slurry to ≥7 during the cleaning process; drying the cleaned slurry at 80-100°C for 10-12h, and then calcining it at 500-550°C for 2-3h to obtain the slurry.

[0026] The present invention also protects a simultaneous reduction of NO X The Cu-based ultra-low temperature catalyst for the reaction of sulfur dioxide and sulfur dioxide is prepared by the above-mentioned preparation method.

[0027] The present invention also protects the above-mentioned preparation method and reduces NO X Application of Cu-based ultra-low temperature catalysts for denitrification of SO2.

[0028] Compared with the prior art, the present invention has the following technical effects:

[0029] The method of the present invention can controllably synthesize the NO X The Cu-based ultra-low temperature catalyst can realize the simultaneous desulfurization and denitrification of NO X , SO2 and CO, while simplifying equipment investment and being compatible with new and existing plant layouts. DETAILED DESCRIPTION

[0030] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.

[0031] Basis for selection of active components: CuO, CoO, and Fe2O3 all have their own redox cycles in the catalytic process. When they work in a synergistic manner, different metal oxides can provide different redox potentials, thereby forming complementary redox cycles in the catalytic process; metal oxides interact with each other through electron transfer, which can promote charge separation and transfer in the reaction, thereby accelerating the catalytic reaction; mixed metal oxides form specific crystal structures or nanostructures, providing a larger specific surface area or specific active sites, thereby enhancing catalytic performance. Higher selectivity is exhibited through synergistic effects. During the catalytic reaction, CuO, CoO, and Fe2O3 metal oxides can undergo redox cycles. This cycle not only promotes NO X The addition of precious metal Pd further accelerates the rate of the redox cycle.

[0032] Basis for carrier selection: The synergistic effect of Al2O3, CeO2, and ZrO2 is mainly achieved through solid solution formation and stability enhancement, complementary redox properties, changes in surface properties, structural effects, and electron transfer and interaction. Al2O3, CeO2, and ZrO2 each have different redox properties. Among them, CeO2, as an oxygen storage material, has excellent redox ability, while ZrO2 and Al2O3 can stabilize the oxidation state of CeO2, thereby maintaining the activity of the catalyst. This complementary redox property can optimize the catalytic performance of the catalyst and form a composite material with specific surface properties. Changes in surface properties are conducive to the adsorption and activation of the substrate, thereby enhancing the catalytic activity.

[0033] Basis for matrix selection: Natural products such as cordierite have sufficient mechanical strength and specific surface area and are easily available.

[0034] CO is a strong reducing agent that can efficiently react with NO under the action of a catalyst. X In the CuO-CoO-Fe2O3-Pd / (Al2O3-CeO2-ZrO2) catalyst system, CO is more easily activated and reacts with NO X Reacts with SO2 to produce harmless N2, CO2 and elemental sulfur.

[0035] In the present invention, NO XThe conversion rate (denitrification efficiency), SO2 conversion rate (desulfurization efficiency) and CO removal rate are determined by measuring the concentration of each substance before and after the reaction, specifically including.

[0036] NO X Conversion rate (denitrification efficiency):

[0037]

[0038] Where, NOxConversion% represents the denitrification efficiency; NO in and NO out They represent NO before entering the reactor. X concentration and NO out of the reactor X concentration.

[0039] CO removal rate:

[0040]

[0041] Where, COConversion% represents the CO removal rate; CO in and CO out They represent the CO concentration before entering the reactor and the CO concentration out of the reactor, respectively.

[0042] NO X Conversion rate (denitrification efficiency):

[0043]

[0044] In the formula, SO2Conversion% represents the desulfurization efficiency; SO 2in and SO 2out They represent the SO2 concentration before entering the reactor and the SO2 concentration out of the reactor respectively.

[0045] Example 1

[0046] In accordance with the above technical scheme, this embodiment discloses a method for preparing a Cu-based ultra-low temperature catalyst for simultaneously reducing NOx and SO2, comprising the following steps:

[0047] Step 1, carrier preparation, Al2O3, CeO2 and SiO2 in a mass ratio of 100:4:310 are mixed to obtain a carrier raw material, ball milled in a ball mill at a speed of 300-600 r / min for 24-36 hours, then placed in a drying oven at 70-110°C for 30 minutes, and then sieved with a 100-mesh stainless steel standard sieve and collected to obtain a carrier powder;

[0048] Step 2, preparation of active components: according to the mass ratio of CuO:CoO:Fe2O3:Pd=2:5:1:0.5, the corresponding Cu(NO3)2·3H2O, Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Pd(NO3)2·2H2O are dissolved in deionized water to prepare an active component solution;

[0049] Step 3, according to the mass ratio of active component to carrier powder of 13:87 and the numerical ratio of active component volume to carrier powder mass of 4:3, the carrier powder obtained in step 1 is immersed in the active component solution obtained in step 2, standing at room temperature for 24 hours, drying at 90-110° C. for 12 hours, and calcining at 700-750° C. for 4 hours to obtain a precursor powder;

[0050] Step 4, mixing the precursor powder and deionized water in a mass ratio of 1:5, adding hydroxymethyl cellulose, and stirring at a constant temperature of 50-100° C. for 3-5 hours to obtain an active slurry;

[0051] Step 5, soaking the cordierite substrate in a 3-5% mass fraction dilute nitric acid solution for 0.5-1.0h, and washing with deionized water to remove residual acid. At the same time, adding ammonia water to make the pH ≥ 7 during the deionized water washing process, and then drying the slurry in an oven at 80°C for 12h, calcining at 500°C for 2h to obtain a pretreated cordierite substrate, and calcining the pretreated cordierite substrate at room temperature, 10 -3 Pa~10 -5 The catalyst was immersed in the active slurry for 2 to 5 hours under a vacuum degree of 1.3 Pa, then dried at 105 to 200°C for 10 to 15 hours, and finally calcined at 500°C for 6 hours to obtain a Cu-based ultra-low temperature catalyst for simultaneously reducing NOx and SO2. The volume ratio of the substrate to the active slurry was 1:3.

[0052] The Cu-based ultra-low temperature catalyst for simultaneously reducing NOx and SO2 prepared in this example was used to carry out a denitration and desulfurization test in the laboratory, and during the test, the concentrations of NOx, SO2 and CO before and after the reaction were measured.

[0053] The conditions of the denitrification test were: 150°C, 5% O2, 12 vol.% H2O, and 50 mg / m 3 、NO X 500mg / m 3 、CO is 1000mg / m 3 、Airspeed 5000h -1 .

[0054] The comparison results of the denitrification efficiency, desulfurization efficiency and CO removal rate of the catalysts are shown in Table 1.

[0055] Example 2

[0056] This embodiment discloses a method for simultaneously reducing NO X A method for preparing a Cu-based ultra-low temperature catalyst for the reaction of SO2 and SO2, the steps of the method are the same as those in Example 1, except that: in this embodiment, in step 1, the carrier raw material component Al2O3:CeO2:ZrO2=100:5:1; in step 2, the corresponding Cu(NO3)2·3H2O, Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Pd(NO3)2·2H2O are dissolved in deionized water according to the mass ratio of CuO:CoO:Fe2O3:Pd=5:6:1.5:0.55; in step 3, the mass ratio of the carrier powder to the active component is 82:18.

[0057] The present embodiment prepared and reduced NO X The Cu-based ultra-low temperature catalyst for denitrification and desulfurization was used to carry out denitrification and desulfurization experiments in the laboratory. During the experiment, the concentrations of NOx, SO2 and CO before and after the reaction were measured.

[0058] The conditions of the denitrification and desulfurization test were: 150°C, 5% O2, 12 vol.% H2O, and 50 mg / m 3 、NO X 500mg / m 3 、CO is 1000mg / m 3 、Airspeed 5000h -1 .Then

[0059] The comparison results of the denitrification efficiency, desulfurization efficiency and CO removal rate of the catalysts are shown in Table 1.

[0060] Example 3

[0061] This embodiment discloses a method for simultaneously reducing NO X A method for preparing a Cu-based ultra-low temperature catalyst for the reaction of SO2 and SO2, the steps of the method are the same as those in Example 1, except that: in this embodiment, in step 1, the carrier raw material component Al2O3:CeO2:ZrO2=100:6:20; in this embodiment, in step 2, the corresponding Cu(NO3)2·3H2O, Co(NO3)2·6H2O, Fe(NO3)3·9H2O, Pd(NO3)2·2H2O are dissolved in deionized water according to the mass ratio of CuO:CoO:Fe2O3:Pd=8:7:2:0.6; in this embodiment, in step 3, the mass ratio of carrier powder to active component is 77:23.

[0062] According to 100g of catalyst powder, its components are: 76.19g Al2O3, 4.57g CeO2, 15.24g ZrO2, 1.82g CuO, 1.59g CoO, 0.45g FeO1.5 、0.14g Pd.

[0063] The Cu-based ultra-low temperature catalyst for simultaneously reducing NOx and SO2 prepared in this example was used to carry out a denitration and desulfurization test in the laboratory, and during the test, the concentrations of NOx, SO2 and CO before and after the reaction were measured.

[0064] The conditions of the denitrification and desulfurization test were: 150°C, 5% O2, 12 vol.% H2O, and 100 mg / m 3 、NO X 500mg / m 3 、CO is 1000mg / m 3 、Airspeed 5000h -1 .

[0065] The comparison results of the denitrification efficiency, desulfurization efficiency and CO removal rate of the catalysts are shown in Table 1.

[0066] Comparative Example 1

[0067] The difference between Comparative Example 1 and Examples 1-3 is that the catalyst is prepared according to the preparation steps of domestic peers (authorization announcement number: CN 116116405 A), the test conditions are the same, and the comparison results of the denitrification efficiency, desulfurization efficiency and CO removal rate of the catalyst are shown in Table 1.

[0068] Comparative Example 2

[0069] The difference between Comparative Example 2 and Examples 1-3 is that the catalyst is prepared according to the preparation steps of domestic peers (authorization announcement number CN 109999804 B), the test conditions are the same, and the comparison results of the denitrification efficiency, desulfurization efficiency and CO removal rate of the catalyst are shown in Table 1.

[0070] Comparative Example 3

[0071] The difference between Comparative Example 3 and Examples 1-3 is that the catalyst is prepared according to the preparation steps of domestic peers (authorization announcement number: CN 115090294 A), the test conditions are the same, and the comparison results of the denitrification efficiency, desulfurization efficiency and CO removal rate of the catalyst are shown in Table 1.

[0072]

[0073] Table 1. Denitrification and desulfurization test results

[0074] As can be seen from Table 1, the catalysts prepared according to the present invention have excellent denitration and desulfurization performance and have broad application prospects. These catalysts can effectively remove nitrogen oxides and sulfur dioxide in exhaust gas, which is of great significance for environmental protection and pollution control.

[0075] On this catalyst system, CO simultaneously reduces NO X The reaction with SO2 may involve multiple pathways. These pathways may include direct reduction, oxidation-reduction cycle, generation and transformation of intermediate species, etc. The diverse reaction pathways jointly promote NO X And efficient reduction of SO2, making.

[0076] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0077] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for simultaneously reducing NO X A method for preparing a Cu-based ultra-low temperature catalyst for SO2, characterized in that: The following steps are involved: Step 1, mixing Al2O3, CeO2 and ZrO2 in a mass ratio of 100:(4-6):(3-4) to obtain a carrier raw material; ball milling, drying and sieving the carrier raw material in sequence to obtain a carrier powder; Step 2, dissolving the active component in a formula amount in deionized water to obtain an active component solution, wherein the active component is compounded from copper salt, cobalt salt, iron salt and palladium salt; Step 3, immersing the carrier powder obtained in step 1 in the active component solution obtained in step 2, and sequentially performing standing, drying and calcining treatments to obtain a precursor powder; Step 4, mixing the precursor powder, the binder and deionized water, and stirring at a constant temperature to obtain an active slurry; Step 5, adding the pretreated substrate to the active slurry for vacuum impregnation to obtain an impregnated product, wherein the volume ratio of the substrate to the active slurry is 1:3; drying and calcining the obtained impregnated product to obtain; In the precursor powder, the mass ratio of the carrier powder to the active component is (77-87): (13~23)。 2. Simultaneous reduction of NO as claimed in claim 1 X A method for preparing a Cu-based ultra-low temperature catalyst for SO2, characterized in that: The carrier raw material is ball-milled, dried and sieved in sequence as described in step 1 to obtain a carrier powder, including: a ball-milling speed of 300 to 600 r / min, a ball-milling time of 24 to 36 h, during the ball-milling process, deionized water is added to the ball mill, and the solid-liquid ratio of the carrier raw material to the deionized water is 1.0:(0.4 to 0.6), and the mass ratio of the grinding balls to the carrier raw material is (5.0 to 10.0):1.0; the drying temperature is 70 to 110° C., and the drying time is 30 min to 60 min; and the powder is sieved through a 100-mesh sieve.

3. The method for preparing a Cu-based ultra-low temperature catalyst for simultaneously reducing NOx and SO2 according to claim 1, characterized in that: The copper salt in the active components is calculated as CuO, the cobalt salt is calculated as CoO, the iron salt is calculated as Fe2O3, and the palladium salt is calculated as Pd, and the mass ratio is CuO:CoO:Fe2O3:Pd=(2-8):(5-7):(1-2):(0.5-0.6).

4. Simultaneous reduction of NO as claimed in claim 1 X A method for preparing a Cu-based ultra-low temperature catalyst for SO2, characterized in that: In step 3, the standing time is 20 to 30 hours; the drying temperature is 90 to 110° C., and the drying time is 12 to 18 hours; the roasting temperature is 700 to 750° C., and the roasting time is 4 to 6 hours.

5. The method for preparing a Cu-based ultra-low temperature catalyst for simultaneously reducing NOx and SO2 according to claim 1, characterized in that: The adhesive is selected from one or more of hydroxymethyl cellulose, polyvinyl alcohol and polyvinyl acetate.

6. Simultaneous reduction of NO as claimed in claim 1 X A method for preparing a Cu-based ultra-low temperature catalyst for SO2, characterized in that: In step 4, the mass ratio of the precursor powder to deionized water is 1:(4.5-5.5), the constant temperature stirring temperature is 50-100° C., and the constant temperature stirring time is 3-5 hours.

7. Simultaneous reduction of NO as claimed in claim 1 X A method for preparing a Cu-based ultra-low temperature catalyst for SO2, characterized in that: In step 5, the vacuum degree of the vacuum impregnation treatment is 10 -3 Pa~10 -5 Pa, the impregnation time is 2 to 5 hours; the drying temperature is 105 to 200°C, and the drying time is 10 to 15 hours; the calcination temperature is 480 to 530°C, and the calcination time is 5 to 8 hours.

8. Simultaneous reduction of NO as claimed in claim 1 X A method for preparing a Cu-based ultra-low temperature catalyst for SO2, characterized in that: The matrix is ​​selected from one or more of a cordierite matrix, a vermiculite matrix, a mullite matrix and a attapulgite matrix; The pretreatment comprises: adding the matrix raw material into a dilute nitric acid solution with a mass fraction of 3-5% and soaking it for 0.5-1.0h to obtain a slurry; circulating deionized water to remove the residual acid in the slurry, and adjusting the pH of the slurry to ≥7 during the cleaning process; drying the cleaned slurry at 80-100°C for 10-12h, and then calcining it at 500-550°C for 2-3h to obtain the slurry.

9. A method for simultaneously reducing NO X A Cu-based ultra-low temperature catalyst for the synthesis of SO2, characterized in that: The method is as described in any one of claims 1 to 8.

10. Use of the Cu-based ultra-low temperature catalyst for simultaneously reducing NOx and SO2 obtained by the preparation method according to any one of claims 1 to 8 in denitration.

Citation Information

Patent Citations

  • A catalyst for CO reduction of SO2, its preparation method and application

    CN109999804B

  • Nickel-based formed catalyst for CO-SCR flue gas denitration and preparation method of nickel-based formed catalyst

    CN115090294A

  • Single-atom cluster type noble metal integral silk screen catalyst for reducing NO from CO

    CN116116405A